Efecto gastroprotector de extractos de centaurea calcitrapa (Veterinary Science, 2017)
The gastroprotective activity of dried heads of Centaurea calcitrapa was studied in mice in whom ulcers had been caused by subjecting them to stress for hypothermia and immobilization. A group of five mice used as control, was administered a mixture of Tween 80 and carboxymethylcellulose by oral via Other three groups, of equal number of animals, and using the same administration via, were treated with aqueous, methanolic and chloroformic extracts resuspended in a mixture of the excipients. The aqueous and methanolic extracts of dry heads of Centauea calcitrapa prevented 100% the damage on the gastric mucosa and the chloroformic extracts inhibited 96.4% (P0.01). These results evidence the metabolites presence with gastroprotective activity in Centaurea calcitrapa
Keywords: Asteraceae; Centaurea calcitrapa; Flavonoids; gastroprotection